Antigen Presenting Cells Contribute to Persistent Immune Activation Despite Antiretroviral Therapy Initiation During Hyperacute HIV-1 Infection - Naidoo, Kewreshini K.; Ndumnego, Okechukwu C.; Ismail, Nasreen; Dong, Krista L.; Ndung’u, Thumbi (Frontiers in Immunology, 2021)
Human immunodeficiency virus (HIV)-induced changes in immune cells during the acute phase of infection can cause irreversible immunological damage and predict the rate of disease progression. Antiretroviral therapy (ART) remains the most effective strategy for successful immune restoration in immunocompromised people living with HIV and the earlier ART is initiated after infection, the better the long-term clinical outcomes. Here we explored the effect of ART on peripheral antigen presenting cell (APC) phenotype and function in women with HIV-1 subtype C infection who initiated ART in the hyperacute phase (before peak viremia) or during chronic infection. Peripheral blood mononuclear cells obtained longitudinally from study participants were used for immunophenotyping and functional analysis of monocytes and dendritic cells (DCs) using multiparametric flow cytometry and matched plasma was used for measurement of inflammatory markers IL-6 and soluble CD14 (sCD14) by enzyme-linked immunosorbent assay. HIV infection was associated with expansion of monocyte and plasmacytoid DC (pDC) frequencies and perturbation of monocyte subsets compared to uninfected persons despite antiretroviral treatment during hyperacute infection. Expression of activation marker CD69 on monocytes and pDCs in early treated HIV was similar to uninfected individuals. However, despite early ART, HIV infection was associated with elevation of plasma IL-6 and sCD14 levels which correlated with monocyte activation. Furthermore, HIV infection with or without early ART was associated with downmodulation of the co-stimulatory molecule CD86. Notably, early ART was associated with preserved toll-like receptor (TLR)-induced IFN-α responses of pDCs. Overall, this data provides evidence of the beneficial impact of ART initiated in hyperacute infection in preservation of APC functional cytokine production activity; but also highlights persistent inflammation facilitated by monocyte activation even after prolonged viral suppression and suggests the need for therapeutic interventions that target residual immune activation.